2017
DOI: 10.1590/1519-6984.12015
|View full text |Cite|
|
Sign up to set email alerts
|

Anatomy and micromorphometric analysis of leaf Catasetum x apolloi Benelli & Grade with addition of potassium silicate under different light sources

Abstract: The aim of this study was to compare vitroplants Catasetum x apolloi grown under natural light and artificial light and different concentrations of potassium silicate, providing data on the anatomical differentiation that aids the acclimatization process of this species. Plants from in vitro seeding were used; 5 protocorms of approximately 0.5 cm were inoculated into vials with a capacity of 500 mL containing 100 mL of alternative culture medium plus potassium silicate (0.0, 0.5; 1.0 mL L -1 ), pH adjusted to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The carbohydrates used during in vitro culture may affect both the morphology/anatomy and physiology of bromeliads (Martins et al, 2015c;Martins et al, 2016aMartins et al, , 2016b. Anatomical analysis of micropropagated plants is an excellent tool to ascertain how the in vitro conditions can affect the success of all the micropropagation stages, including transfer to ex vitro conditions (Martins et al, 2015c;Eburneo et al, 2017). Studies have also measured the chlorophyll a fluorescence to determine the performance of the photosynthetic apparatus of plants grown in vitro (Dobránszki and Drienyovszki, 2014;Matysiak and Gabryszewska, 2016;Rosa et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The carbohydrates used during in vitro culture may affect both the morphology/anatomy and physiology of bromeliads (Martins et al, 2015c;Martins et al, 2016aMartins et al, , 2016b. Anatomical analysis of micropropagated plants is an excellent tool to ascertain how the in vitro conditions can affect the success of all the micropropagation stages, including transfer to ex vitro conditions (Martins et al, 2015c;Eburneo et al, 2017). Studies have also measured the chlorophyll a fluorescence to determine the performance of the photosynthetic apparatus of plants grown in vitro (Dobránszki and Drienyovszki, 2014;Matysiak and Gabryszewska, 2016;Rosa et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Plants grown in the first condition showed higher epidermal thickness, leaf mesophyll thickness, root velamen thickness, and stomatal density. Moreover, EBURNEO et al (2017) reported that Catasetum x apolloi Benelli & Grade stomata responded better to water stress when the orchid grew in a natural light environment.…”
Section: Introductionmentioning
confidence: 99%